Insomnia in Patients Seeking Care at an Orofacial Pain Unit - Meira e Cruz, Miguel; Lukic, Nenad; Wojczynska, Aleksandra; Steiger, Beat; Guimarães, Antonio Sérgio; Ettlin, Dominik A. (Frontiers in Neurology, 2019)
Introduction: Orofacial pain and dysfunction include a broad range of disturbances among which pain and insomnia are some of the most common complaints. Sleep strengthens physiological and psychological resilience and is an absolute requirement for health. Insomnia is a common symptom or sleep disorder, yet data on its prevalence is sparse. Here we extracted data from the insomnia severity index which was part of the web-based interdisciplinary symptom evaluation tool given to a large sample of patients seeking care at an orofacial pain unit for analyzing insomnia prevalence in this clinical population. Material and methods: Anonymized data were available from 952 patients who consulted the Orofacial Pain Unit at the Center of Dental Medicine, University of Zurich, Zurich, Switzerland between January 2017 and December 2018. Prevalence data for insomnia stratified by gender and ten age groups (decades) were calculated. The distribution of four insomnia severity grades was determined, also stratified by age and gender. Results: 952 patients (290 men: 30,5%) with a mean age of 44.8 ±17.4 years completed a web-based interdisciplinary symptom evaluation. 352 (37.0%) patients with a mean age of 45.8 ±16.7 years positively responded to a screening question for insomnia and/or hypersomnia. Insomnia was severe in women from the 2nd to 8th decade, ranging from 4.3 % (3rd decade) to 14.5% (6th decade) and moderately severe from the 2nd to 9th decade, ranging from 18.8 % (6th decade) to 27.8% (2nd decade). In men, severe insomnia was present from the 3rd to 7th decade, ranging from 2.3 % (7th decade) to 4.4% (4th decade) and moderately severe insomnia from the 3rd to 7th decade, ranging from 4.6 % (7th decade) to 12.2% (5th decade). Conclusions: This is the first study reporting on insomnia in a large sample of patients seeking care at an orofacial pain unit. One in three patients reported some form of sleep disturbances , which for almost half of them was moderate to severe insomnia. The gender ratio was almost equal throughout adulthood, yet younger and older women were more frequently affected and experienced higher insomnia severity than men.